Influence of coconut fiber on the microstructural, mechanical and hydraulic behavior of unsaturated compacted soil - Gomes, Fernanda Santos [UNESP]; Motta, Mariana Ferreira Benessiuti [UNESP]; Bernardes, George De Paula [UNESP]; Soares, Paulo Valladares [UNESP] (Associação Brasileira de Mecânica dos Solos, 2023)
This study aimed to evaluate the influence of the addition of coconut (coir) fibers on the microstructural, hydraulic and mechanical behavior of an unsaturated compacted soil. Specimens were molded and compacted, forming composites with 0%, 0.1%, 0.5% and 1% fiber in relation to their dry mass. The characterization of pores from the soil and fiber soil mixtures was performed by the Mercury Intrusion Porosimetry tests. Suction values were obtained through the filter paper method and soil water retention curves were adjusted with the Durner model due to the bimodal behavior. Tensile strength values were obtained from the indirect tensile strength test (Brazilian tensile test) for specimens with different suction values. It was found that the increase in fiber content in the material lead to a non-linear increase in macropores, which affected both the hydraulic and mechanical behavior of the soil. Furthermore, the shape of the soil water retention curve was preserved, but there were changes in the values of first and second air entry and residual suction. The tensile strength was negatively influenced, reaching a reduction of about 30% in the situation with higher fiber content. However, for higher levels, the behavior of the soil changed from brittle to ductile, increasing the supported deformations.
Keywords: Coconut fiber; Unsaturated soil; Compacted soil; Mercury intrusion porosimetry; Soil water retention curve; Tensile strength